Combustion technique synthesis of lead-free piezoelectric bismuth sodium titanate-bismuth potassium titanate–barium titanate ceramics. Issue 175 (12th October 2016) - Thongtha, Atthakorn; Bongkarn, Theerachai
ABSTRACT: Fabrication of lead-free piezoelectric ceramic bismuth sodium titanate–bismuth potassium titanate–barium titanate, focusing on the morphotropic phase boundary (MPB) between the rhombohedral and tetragonal phases was studied. a [0.935(Bi0.5 Na0.5 )TiO3 -0.065BaTiO3 ]-(1- a )[0.8(Bi0.5 Na0.5 )TiO3 -0.2(Bi0.5 K0.5 )TiO3 ]; BNBK ceramics with 0 ≤ a ≤ 1 were successfully fabricated using the combustion technique. All BNBK samples were sintered at 1150 °C for 2 h. The effect of a changing on the phase formation, microstructure, dielectric properties and piezoelectric properties of perovskite BNBK ceramics were investigated. XRD results of BNBK ceramics with 0 ≤ a ≤ 1 showed the rhombohedral-tetragonal morphotropic phase boundary (MPB). The SEM results showed the average grain size is between 1.18 and 2.56 µm. The effect of the a content had no influence on the tendency of grain sizes. The maximum density, shrinkage, dielectric constant at Curie temperature (ϵr ), remanent polarization (Pr ), coercive field (Ec ) and piezoelectric constant (d33 ) were found from BNBK ceramic with a = 1, which is around 5.76 g/cm 3, 18.43%, 6503, 15.4 μC/cm 2, 20.1 kV/cm and 289 pC/N, respectively.